(untitled) (Scientific journal of the Fergana State University, 2024)
Information is given on the influence of certain factors on the growth, development, productivity and chemical composition of plants growing in the reservoirs of the Karadarya, as well as on their use in the national economy. To facilitate the study of plants growing in water, they are first divided into three large groups; plants that float in water, plants that grow half submerged in water, and plants that grow in an aquifer. The study of unexplored or poorly studied flora of wetlands and wetlands of the Karadarya basin was aimed at developing a modern wetland system. To do this, the goal is to analyze the available data on higher aquatic and wetland plants in literary sources; collect samples (herbariums) of higher aquatic and wetland plants in natural and artificial reservoirs of the river basin and identify it. Among aquatic and wetland plants there are many forage, building, medicinal vitamin, honey-bearing, starchy, decorative species. The demand for raw materials for aquatic plants is growing every day. More than 240 samples of higher aquatic and wetland plants from the Karadarya basin were collected, and as a result of their analysis, 114 species belonging to 4 divisions, 5 classes, 12 classes, 25 genera, 29 families, 47 genera were identified. Among them are the leading families Cyperaceae (19 species), Poaceae (21 species), Typhaceae (8 species), Potomagetone (6 species). High-water and wetland plants have been identified in forage, construction, medicinal, vitamin, honey - succulent plants. there are many starchy, decorative species. In the future, it is advisable to identify promising species among them and study their bioecological features in the conditions of introduction, develop methods of gross reproduction and introduce them into the national economy.